PENGETAHUAN LOKAL NELAYAN BUGIS DALAM ESTIMASI JARAK DAN WAKTU: KAJIAN ETNOMATEMATIKA PADA AKTIVITAS MELAUT - Sri Wahyuni; Zulfiqar Busrah; Andi Aras; Azmidar Azmidar (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This study aims to uncover the concept of ethnomathematics in the practice of distance and time estimation in the fishing activities of Bugis fishermen on the coast of Cempae, Parepare City. The study used a qualitative approach with ethnographic methods. Data were obtained through participatory observation and in-depth interviews with three informants, then analyzed using the Spradley model which includes domain analysis, taxonomy, components, and cultural themes. The results show that fishermen utilize local knowledge in determining direction, distance, and time through natural signs such as islands, seabirds, water color, and the position of the sun (lettu esso ri ulunna). Four main domains were found, namely determining position using islands and seabirds as directional references, determining distance based on fishing experience, determining time through the position of the sun and weather conditions, and observing marine environmental conditions through water color and ocean currents. These four domains are interrelated in supporting fishermen's fishing activities. The cultural theme reveals the integration of local knowledge with mathematical concepts through measuring, counting, locating, and designing activities. The estimation carried out by fishermen remains relevant because it is contextual and adaptive.